Sikap dan Perilaku Mahasiswa dalam Memilah Sampah Organik dan Anorganik di UINSU - Nazwa Alya Alkhansa; Soviani Soviani; Nurul Rizkia; Mas Imam Temuju; Sari Wulandari (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
The purpose of this study was to determine the behavior and way of thinking of students of the State Islamic University of North Sumatra (UINSU) in sorting organic and inorganic waste in the campus environment. This study combines descriptive methods with a qualitative approach. The methods used to obtain data are direct observation, in-depth interviews, and documentation. The subjects of this study were students from various faculties and campus environmental cleaners. The results of the study showed differences in students' views and actions in sorting waste. Despite having a positive attitude towards environmental issues, most students have not implemented waste sorting behavior consistently. The inhibiting factors found include limited facilities, lack of environmental education, and weak institutional supervision. Recommendations in this study include the provision of adequate facilities, ongoing education, and the formation of an active environmental care community in the UINSU environment.